La pedagogía constructivista frente a la educación tradicional en la enseñanza - aprendizaje en niños y niñas de preparatoria - Chuchuca López, Indira Belén; Loja Quituizaca, Diana Jamilette (Machala, 2022)
Currently, the teaching-learning process allows finding and rediscovering ways to teach students, since from the beginning of their lives they develop stages that will allow them to learn through their senses, movements, social relationships, experiences, among others. As they grow, they are constantly building the foundations of their knowledge through physical and social interaction with their peers and environment; for this reason, it is eminent that teachers use constructivist pedagogy in the classroom, since this current proposes an education based on the development of skills and abilities for meaningful learning in children. In this interpretation, the main objective of this research is to determine how the constructivist pedagogical mode promotes a more meaningful education as opposed to the traditionalist model. The methodology used has a quantitative approach, which allowed collecting, analyzing and interpreting the information obtained from the hypothetical deductive method; the research has a descriptive correlational design. The population was made up of 3 teachers and 87 children, of which the selected sample corresponded to 2 educators and 25 students; To obtain the information, a semi-structured interview and an observation sheet addressed to the children in the institution where the research was carried out were used as a technique and instrument. The results of this research project confirm that there is a relationship between Constructivist Pedagogy and Traditional Education, for which the theoretical foundation of scientific articles by authors of the constructivist current was taken as a reference. It is concluded that the application of constructivist pedagogy in the educational context favors and facilitates the acquisition and constant construction of learning in the students.
En la actualidad el proceso de enseñanza- aprendizaje permite encontrar y redescubrir las maneras de enseñar a los educandos; ya que desde inicio de su vida va desarrollando etapas que le permitirá aprender por medio de sus sentidos, movimientos, relaciones sociales, experiencias, entre otras. A medida que va creciendo va construyendo constantemente las bases de su conocimiento a través de la interacción física y social con sus pares y entorno; por tal motivo es eminente que los docentes empleen en el aula de clases la pedagogía constructivista, dado que esta corriente propone una educación basada en el desarrollo de habilidades y destrezas para un aprendizaje significativo en los niños. En esta interpretación se plantea como objetivo principal de esta investigación, determinar de qué manera el modo pedagógico constructivista fomenta una educación más significativa frente al modelo tradicionalista. La metodología utilizada tiene un enfoque cuantitativo, lo cual, permitió recolectar, analizar e interpretar la información obtenida partiendo del método hipotético deductivo; la investigación posee un diseño descriptivo correlacional. La población se constituyó por 3 docentes y 87 niños, de la cual la muestra seleccionada correspondía a 2 educadoras y 25 estudiantes; para obtener la información se utilizó como técnica e instrumento una entrevista semiestructurada y una ficha de observación dirigida a los niños en la institución que se realizó la investigación. Los resultados del presente proyecto investigación, confirman que existe relación entre la Pedagogía Constructivista frente a la Educación Tradicional, para lo cual se tomó como referencia la fundamentación teórica de artículos científicos de autores de la corriente constructivista. Se concluye que el aplicar la pedagogía constructivista en el contexto educativo, propicia y facilita la adquisición y construcción constante de aprendizaje en los educandos.
Keywords: PEDAGOGIA CONSTRUCTIVISTA; APRENDIZAJE SIGNIFICATIVO